Optimasi Konsentrasi Span 80 dan Lama Pengadukan dalam Preparasi Microspheres Metformin Hidroklorida-kitosan (Optimization of Span 80 Concentration and Stiring Time on The Preparation of Metformin Hydrochloride-Chitosan Microspheres ) - Christyn Novita S; Lusia Oktora Ruma Kumala Sari; Eka Deddy Irawan (Pustaka Kesehatan, 2018)
Metformin hydrochloride (MH) has been used as first line for type 2 diabetes mellitus treatment. However, it has relatively low bioavailability, short half-life and could cause gastrointestinal side effects, therefore it is appropriately prepared as microspheres. Microspheres is micro particle which is between 1-1,000 µm in size. Many factors affected the result of microspheres preparation, such as surfactant concentration and stirring time. This research was aimed to find the best composition of span 80 concentration and stirring time to produce MH-chitosan (CH) microspheres with the highest entrapment efficiency (EE) using factorial design optimization. MH was used as active substance, CH as polymer, span 80 as surfactant and non-aqueous solvent evaporation method was chosen for microspheres preparation technique. The optimized formula 2 % span 80 and 2 hours stirring time gained 86.803 ± 0.544 % EE, 24.571 ± 0.157 % drug loading, and 88.220 ± 0.137 % yield. The microspheres had a relatively smooth, bright surface, and spherical structure. The average particle’s size was 161.2 ± 1.743 μm. FTIR analysis indicated that there were no changes in the spesific functional clusters of MH as an active substance. Keywords: metfomin-hydrocloride-chitosan microspheres, non-aquoeous solvent evaporation, factorial design, span 80 concentration, stirring time.